P-OGC41 Survival after curative chemoradiotherapy or neoadjuvant therapy and surgery converges in higher-risk patients with oesophageal cancer. (16th December 2021) - Rana, Mridul; Sanga, Akshata; Sgromo, Bruno; Gillies, Richard; Marshall, Robert; Maynard, Nick; Ash, Stephen; Antonowicz, Stefan; Owen, Richard
Abstract: Background: Both curative chemoradiotherapy (cCRT) and neoadjuvant chemoradiotherapy and surgery (nCRTS) can be considered as treatments for potentially curable oesophageal squamous cell carcinoma (OSCC). Whilst this equipoise does not exist in oesophageal adenocarcinoma (OAC), there are patients in whom treatment decisions are not straightforward, creating an overlapping group in which cCRT might be considered in preference to neoadjuvant chemotherapy or chemoradiotherapy and surgery (nC(R)TS). We aim to see how survival changes between unmatched and matched cohorts of patients with OAC and OSCC treated with cCRT or nC(R)TS, to reflect difficult multidisciplinary team treatment decisions. Methods: Patients treated with nC(R)TS or cCRT for OSCC and OAC were identified on an intention-to-treat basis from April 2016 to April 2019, allowing a minimum 2-year follow up from diagnosis. Upper third tumours were excluded due to clear preference for cCRT. Preoperative variables were compared using descriptive statistics, with OSCC and OAC analysed separately. Significantly different variables were used to generate propensity scores. Cohorts were then matched and analysis repeated to assess cohort symmetry. Overall survival and 2-year survival were investigated using Kaplan-Meier survival curves and log-rank testing. Analysis was performed in R. Results: 60 and 231 patients with OSCC and OAC were treated with cCRT or nC(R)TS. In the unmatched analysis, nC(R)TS had superior overall and 2-year survival, however there were significant differences in age, Charlson comorbidity index and cancer stage in OSCC and OAC cohorts, and in tumour site for the OAC cohort. After propensity score matching, differences in overall and 2-year survival reduced, though no results reached significance (OSCC: nCRTS 2y survival 58% vs 51% and 54% in unmatched and matched cCRT cohorts, respectively; OAC: cCRT 2y survival 51% vs 60% and 56% in unmatched and matched nC(R)TS cohorts, respectively). Conclusions: These data suggest that as patient and cancer related factors increase the difficulty of treatment decisions, the survival benefit of surgery reduces in both OSCC and OAC. These results underline the need for randomised controlled trials using current treatment and staging strategies, as there have been considerable advances since original comparisons of neoadjuvant and curative chemoradiotherapy. This study is limited by relatively short follow up and unpowered sample sizes, however the coded nature of the analysis provides a structure for regular review of outcomes in our unit using routinely collected data, and could be easily applied more widely.